Germany : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper examines Germany's growth record in 1992-2001 and analyzes how future performance might be enhanced. The paper focuses on the longer-term strains on the public finances. It reviews Germany's external competitiveness, which deteriorated substantially in the wake of unification, and concludes that, by the beginning of the current decade, competitiveness had been largely restored. The paper also examines the recent slowdown in credit, which has gone beyond what might be expected on cyclical grounds.